59 minutes : a novel - Seddon, Holly (Emily Bestler Books/Atria, 2025)
"Carrie is a young mother desperate to reunite with her daughter. Frankie, newly pregnant, faces a romantic vacation that takes a terrifying turn. Then there's the enigmatic older woman determined to protect her teenage daughter, Bunny, no matter what.Across South England, these three women must navigate survival amidst chaos when the country receives a nuclear bomb alert. With only 59 minutes before mass destruction, will they make it to their loved ones in time?"--